The Effect of Integrative Curriculum Implementation and Character Education on Academic Success of Islamic Boarding School Students in East Java - Riyadi, Slamet; Nasruddin, Nasruddin; Miftachurohmah, Nisa (Westscience Press, 2024)
This study investigates the impact of integrative curriculum implementation and character education on the academic success of students in Islamic boarding schools in East Java. Utilizing a quantitative research design, the study gathered data from a sample of 150 students, employing a Likert scale ranging from 1 to 5 to measure responses. The analysis was conducted using SPSS version 25 to determine the relationship between the variables. Findings reveal a significant positive effect of both integrative curriculum and character education on academic performance. Integrative curriculum implementation (r = 0.64, p < 0.01) and character education (r = 0.58, p < 0.01) were both positively correlated with academic success. Multiple regression analysis showed that these variables together explained 52% of the variance in academic success. The results underscore the importance of a holistic educational approach that combines academic and character development to enhance student outcomes. These insights offer valuable implications for educators and policymakers aiming to improve educational strategies in Islamic boarding schools.